The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.46881/ajsn.v6i0.142
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Efficiency Among Rice Farmers in Oyo State, Nigeria

Abstract: Increased rice productivity for years is not a solution if rice farming efficiency cannot be sustained for the next hundred years. The study analysed the efficiency of rice farmers in Oyo State. A multistage sampling procedure was employed to select128 rice farmers for the study. Primary data were obtained with the aid of well-structured questionnaire and interview schedule. Descriptive statistics and stochastic frontier model were employed in the analysis of the data. Majority (78.1%) of the rice farmers had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Various demographical factors such as the age of the learners, socioeconomic activities and occupation affect the participation of adults in learning programmes, Adeshina & Idowu (2013) concluded that funding and creation of adult learning centers better at shorter distances and it creates more access. It thus helps adult learners with these demographical challenges to participate in learning programmes.…”
Section: Introductionmentioning
confidence: 99%
“…Various demographical factors such as the age of the learners, socioeconomic activities and occupation affect the participation of adults in learning programmes, Adeshina & Idowu (2013) concluded that funding and creation of adult learning centers better at shorter distances and it creates more access. It thus helps adult learners with these demographical challenges to participate in learning programmes.…”
Section: Introductionmentioning
confidence: 99%